THE EFFECT OF GOOD CORPORATE GOVERNANCE, LEVERAGE, AND PROFITABILITY ON RETURNS IN STOCK - Hidayah, Hikmawatul; Juliasari, Deni; Ifa, Khoirul (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2021)
Return Stockis the reciprocal result of stock investment activities that will be received by investors. Before investing in stocks, investors must analyze the company from a financial and non-financial perspective. The purpose of this study is to examine and analyze the effect of good corporate governance, leverage, and profitability on returns stockin manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2019. The data needed in this study is secondary data in the form of annual reports of manufacturing companies. published by the Indonesia Stock Exchange in the period 2017 to 2019 through the website www.idx.co.id. The sampling technique used is purposive sampling. The technique of data analysis uses multiple linear regression analysis which is processed with the SPSS application. The results of the analysis of this study indicate that 1) good corporate governance (CGPI scoring) has no significant effect on stock returns, 2) leverage (Debt to Equity Ratio) has no significant effect on returns stock, 3) Profitability (Return on Equity) has a significant effect on return.